ANALISIS KEGIATAN BAHTSUL MASAIL MATERI FIQIH DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SANTRI DI PONDOK PESANTREN ULUMUL QUR’AN AL-QINDILIYYAH KALIBEBER, MOJOTENGAH, WONOSOBO - Hastari, Ririn; Sidiq, Ngarifin; Alawiyah, Luluk (AL-QALAM: JURNAL KEPENDIDIKAN, 2019)
This study aims to determine: (1) the implementation of bahtsul masail fiqih material activities at the Ulumul Qur’an Al-Qindiliyyah Boarding School (2) The role of bahtsul masail fiqih material activities in improving students thinking skills at the Ulumul Qur’an Al-Qindiliyyah Boarding School (3) The inhibiting factors for the implementation of bahtsul masail fiqih material activities at the Ulumul Qur’an Al-Qindiliyyah Boarding School. The method used is field research with a qualitative approach. Collecting data using interview, observation, and documentation methods. Data analysis techniques used are: data reduction data presentation, and drawing conclusions. The results showed that the bahtsul masail fiqih material at the Ulumul Qur’an Al-Qindiliyyah Islamic Boarding School had several components and stages. Improving students critical thinking skills through bahtsul masail fiqh activities can be seen from the ability to understand and describe problems, search for answers based on strong and relevant sources, identify and analyze answers based on the relationship to the problems discussed, and determine the most appropriate answer as a solution to the problem. The implementation of the bahtsul masail fiqih material encountered several obstacles such as the level of courage and self-confidence of the studens was still low, the reference sources for the answers were incomplete, the studens ability and interest in reading the yellow book were not maximal, and the arrival of students in the bahtsul masail forum was not on time.